Escherichia coli O157:H7—Clinical aspects and novel treatment approaches - Rahal, Elias A.; Kazzi, Natalie; Nassar, Farah J.; Matar, Ghassan M. (Frontiers in Cellular and Infection Microbiology, 2012)
Escherichia coli O157:H7 is a notorious pathogen often contracted by intake of contaminated water or food. Infection with this agent is associated with a broad spectrum of illness ranging from mild diarrhea and hemorrhagic colitis to the potentially fatal hemolytic uremic syndrome (HUS). Treating E. coli O157:H7 infection with antimicrobial agents is associated with an increased risk of severe sequelae such as HUS. The difficulty in treating this bacterium using conventional modalities of antimicrobial agent administration has sparked an interest in investigating new therapeutic approaches to this bacterium. These approaches have included the use of probiotic agents and natural products with variable success rates. In addition, novel modalities and regimen of antimicrobial agent administration have been assessed in an attempt at decreasing their association with aggravating infection outcomes.